Exploring the Correlation of Recognizing Proof Techniques and Definitions (Theorems) on the Ability of Indonesian Students in Mathematical Proof - Junarti, Junarti; Simamora, Rianita; Abu Hassan, Nurul Nadiya (Jurnal Pendidikan Edutama, 2024)
The aim of this research is to measure the extent of the correlation between the ability to recognize proof techniques and the ability to recognize definitions/theorems with the ability to prove in the Real Analysis course. This study tests the associative hypothesis of two independent variables (the ability to recognize proof techniques and definitions/theorems) with one dependent variable (the ability in mathematical prove). The research sample consists of a total of 60 students currently enrolled in the real analysis course. The study was lecture-based, involving tasks such as identifying proof techniques in provided proofs from textbooks, writing definitions/theorems in proofs, and conducting proof tests to measure proof abilities. Subsequently, the data was analyzed using a multiple correlation test between the two independent variables and one dependent variable with the assistance of SPSS version 25. The correlation coefficient obtained is 0.821, indicating a very strong relationship between the ability to recognize proof techniques and the skill of recognizing definitions/theorems together with the ability to prove.